Strategi transformasi digital pada Lembaga Keuangan Mikro Syariah (LKMS) - azzahra, fathia (Maliki Interdisciplinary Journal, 2025)
The digital era has brought major changes to the Islamic financial system in Indonesia. Technological developments such as artificial intelligence, blockchain, and financial technology have encouraged Islamic financial institutions to adapt through planned and sustainable digital transformation. This transformation is a strategic step for Islamic Microfinance Institutions (LKMS) to survive economic disruption and improve operational efficiency. Digitalization provides vast opportunities to strengthen financial inclusion, accelerate services, and expand public access to Islamic-based financial products. However, the application of technology must remain grounded in the values of maqashid sharia, which emphasizes justice, benefit, and the welfare of the people. In addition to commercial institutions, Islamic social institutions such as BAZNAS and BWI have also implemented digital systems in the management of zakat, infaq, sadaqah, and waqf, thereby increasing the transparency and effectiveness of social fund distribution. Examples of implementation at BMT UGT Sidogiri and BMT Surya Madani show that digitization can improve performance, expand services, and strengthen the competitiveness of institutions. Thus, digital transformation is a strategic necessity for Islamic financial institutions to create a sustainable, inclusive financial ecosystem that is in line with Islamic values.